Removing noises caused by motion artefacts in microcirculation maps of human skin in vivo. (10th September 2015) - CHEN, C.; SHI, W.; GAO, W.
Summary: This paper presents a zero‐padding and cross‐correlation technique‐based correlation mapping optical coherence tomography (ZPCC‐cmOCT) to reconstruct microcirculation maps of human skin in vivo, which can remove the background decorrelation noise caused by motion artefacts. In conventional correlation mapping optical coherence tomography method, the correlation degree of static tissue may be lowered by the motion artefacts due to cardiac and respiratory motion, resulting in background decorrelation noise in microcirculation maps. In zero‐padding and cross‐correlation technique‐based correlation mapping optical coherence tomography method, structural images are first obtained by performing Fourier transform on zero‐padded interference fringes, and then cross‐correlation‐based image registration is utilized to align local areas in two adjacent structural images. Finally, correlation mapping optical coherence tomography method is performed to generate microcirculation maps. Both phantom experiments and in vivo experiments were implemented and the results demonstrate that the proposed method is capable of providing microcirculation maps with the background decorrelation noise removed.